A High-Pulse-Energy High-Beam-Quality Tunable Ti：Sapphire Laser Using a Prism-Dispersion Cavity - 许昌 代世波 郭川 卞奇 左军卫 夏元钦 高宏伟 王志敏 薄勇 宗楠 张盛 彭钦军 许祖彦 (Chinese physics letters, 2017)
A high-pulse-energy high-beam-quality tunable Ti：sapphire laser pumped by a frequency-doubled Nd：YAG laser is demonstrated. Using a fused-silica prism as the dispersion element, a tuning range of 740-855 nm is obtained. At an incident pump energy of 774mJ, the maximum output energy of 104mJ at 790nm with a pulse width of 100μs is achieved at a repetition rate of 5 Hz. To the best of our knowledge, it is the highest pulse energy at 790 nm with pulse width of hundred micro-seconds for an all-solid-state laser. The linewidth of output is 0.5 nm, and the beam quality factor M2 is 1.16. The high-pulse-energy high-beam-quality tunable Ti：sapphire laser in the range of 740-855 nm can be used to establish a more accurate and consistent absolute scale of second-order optical-nonlinear coefficients for KBe2BO3F2 measured in a wider wavelength range and to assess Miller＇s rule quantitatively.